SPECIFIC INTERESTS OF THE NORTH CAUCASIAN ELITES AS A CONFLICT POTENTIAL - SALGIRIEV, Ali; BETILMERZAEVA, Maret; SOLTAMURADOV, Magomed; Emi SHAMSUEV, Magomed (CENTRAL ASIA AND THE CAUCASUS, 2018)
The authors have studied the main potentially conflicting factors of the regional ethnopolitical elites’ actions in their respective regions, traced the emergence and development of these factors, and sorted out the origins of conflicts and their escalation using the Northern Caucasus as an example. The region’s economic backwardness, poverty, unemployment, and social differentiation are considered the main sources of potentially conflicting behavior. Much attention is paid to indirect indicators of the local population’s standard of living. Regional stability is threatened, first and foremost, by the local elite’s clan and tribal organization principles and the mechanism of new member incorporation that excludes the majority of the local younger generation from adequate employment that would help them realize their educational and professional potentials. So far, the regional political system is developing as paternalist and traditionalist, and is replenished from channels inaccessible to common people; this causes well-justified irritation and lowers the level of institutional trust. To remain in control of power distribution in clans and cliques, the regional elites relied and are still relying on the ethnic mobilization potential. The archaic replenishment mechanisms and the low quality of the ruling elites are responsible, to a great extent, for the region’s depressive economies. The authors have thoroughly described how those determined to remain in power invent myths and use them as a brainwashing instrument. People have not yet disentangled themselves from the web of traditional practices and pagan prejudices. This is confirmed by numerous examples of the mythologization of public consciousness and speaks volumes of the fairly low educational and cultural levels of the local population. In conclusion, the authors recommend blocking out conflict behavior for the sake of a smoothly functioning political system in the region. To achieve this goal, corruption should be finally curbed, while transparency should become an inalienable characteristic of elections and power institutions. The region needs more jobs in all economic sectors; its industry should be revived at a faster pace, while the tourist sector should become more attractive. The Northern Caucasus should be fully integrated into the common social and cultural space by tuning up interregional cooperation and working out a more balanced information policy designed to prevent all forms of discrimination, first and foremost, religious and ethnic. The economic agenda cannot be addressed until all political tasks—security, uncompromising struggle against corruption in all spheres, including the judicial, nepotism, and strict observance of human and civil rights—have been resolved.